AI-based Analysis on Relationship between Genes and Personality: Evaluation Results with the ABO Blood Type - Kanazawa, Masayuki (Transactions on Engineering and Computing Sciences, 2021)
AI can be applied in various ways to the measurement of personality in psychology. Measuring the impact of a single gene on personality can be handled by AI technologies, at least technically, i.e., using supervised learning models of machine learning. The ABO blood type is a relatively easy biological marker to examine; therefore, people in many countries know their type, and its impact on the relationship with personality has been the subject of a large amount of research. In this study, we selected the ABO blood type as the target gene, examined its association with personality, and cross-checked the results with previous works. Two scales were used to measure personality: a) blood type personality traits extracted from previous studies, and b) the TIPI-J, a simplified version of the Big Five personality test. In the former, the AI was able to predict the respondents’ blood types with a higher probability than chance, while in the latter, the accuracy was within the range of chance. These obtained results were also discussed.